Assessing the Efficacy and Mechanisms of Pycnogenol® on Cognitive Aging From In Vitro Animal and Human Studies - Simpson, Tamara; Kure, Christina; Stough, Con (Frontiers in Pharmacology, 2019)
Brain ageing is a complex and multi-factorial process broadly involving changes in the brain’s structure, neuronal activity and biochemical profile. These changes in brain function have also been linked to age associated variations in cognitive function. Recent research has suggested a role of increased oxidative stress and reduced cognition in older people. Therefore, studies which examine the effects of antioxidants on cognitive performance are important, particularly in the context of an increase in elderly populations in most Western countries. One such antioxidant, Pycnogenol, is a standardised plant-based extract obtained from the bark of the French maritime pine and has a long historical use to treat inflammation and improve health. More recently, Pycnogenol, has been subjected to more than 100 research trials. In vitro and animal studies using the standardised extract have indicated a multimodal action of Pycnogenol and several human studies have shown improvements in cognitive function after chronic administration. In this paper, we review these studies in the context of understanding both biological and cognitive changes due to Pycnogenol and evaluate possibilities of Pycnogenol to improve neurocognitive function.